PEER REJECTION IN STUDENT LIFE & HOW WE CAN HELP OUR STUDENT - Irmadatus Sholekhah; Dibyo Waskito Guntoro (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
This article discusses how to rejected students seen from various opinions of students with popular and controversial status. Observations were made on students in Junior High Schools who received responses from their social environment. The aim is to find out the factors that are considered a peer. Furthermore, this article tries to reveal how students are rejected in their daily lives outside the classroom, before on matters not approved by the teacher. This research is a qualitative study using in-depth interviews to collect the data. The sample is using snowball sampling, then was analyzed by quantitative analysis. The results show that rejected student who have peer rejection tend to have aggressive behavior that disturbs their classmates. This group experienced rejection from its social environment because of bad habits and more often doing bullying (both verbally and physically). These results contribute to the teacher be able to recognize their students better.